Cone-Rod Dystrophy Caused by a Novel Homozygous RPE65 Mutation in Leber Congenital Amaurosis - Jakobsson, C.; Othman, I. S.; Munier, F. L.; Schorderet, D. F.; Abouzeid, H. (Klinische Monatsblätter für Augenheilkunde, 2014)
Background: The aim of this study was to describe an unexpected phenotype in a family with Leber congenital amaurosis (LCA) due to a retinal pigment epithelium-specific protein 65 kDa (RPE65) homozygous mutation.History and Signs: We analyzed a family from Yemen in which 3 individuals were affected with LCA. Linkage analysis using markers flanking the known LCA genes was done, followed by direct sequencing of RPE65.Therapy and Outcome: Severe visual impairment and night blindness were observed during infancy. We observed photophobia only in the 8-year-old patient. The youngest affected had bilateral hyperopia of + 3.50 and visual acuity of 1/60. The oldest two had visual acuity limited to hand movements in the right eye (OD) and counting fingers in the left eye (OS) for the oldest and of 5/60 OD, 6/60 OS for the other. They showed disc pallor, attenuated vessels, white flecks in the retina mid-periphery and bullʼs eye maculopathy. ERGs of the oldest child were completely unresponsive. Genomic sequencing identified a novel homozygous missense mutation, IVS2-3C > G, in the second RPE65 intron.Conclusions: We identified a novel LCA-related homozygous RPE65 mutation associated with a severe clinical presentation including an early and severe cone dysfunction. This is in contrast with the presentation associated with other RPE65 mutations predominantly causing rod-cone dystrophy with residual visual function.
Keywords: Leber congenital amaurosis; RPE65; cone-rod dystrophy; genetics.